Periapical pocket cyst of anterior maxilla: A case report and literature review - Mounika Sathiya; Hemavarshini Shanmugalingham; Hemalatha Balasubramanian; C J Harisudhan; S Harini; Bose Divya (Wolters Kluwer Medknow Publications, 2020)
Periapical cyst is an inflammatory odontogenic cyst of endodontic origin. It is called as periapical true cyst when the cyst is epithelium lined, closed pathological cavity or periapical pocket cyst when the epithelium lined cavity is continuous with the root canal of the affected tooth. Majority of the periapical cyst has the potential to heal after conventional root canal treatment. Large, true cysts respond less favorably to nonsurgical treatment. We present a case of 24 year old male patient who presented with a swelling in the upper lip region. A diagnosis of periapical cyst was made based on clinical and radiographic features. Intraoperatively, the cyst was found to be continuous with the root canal. Considering the histopathological features, a final diagnosis of periapical pocket cyst was given.